Matter wave compactons in deep optical lattices with strong nonlinearity management - Salerno, Mario; Abdullaev, Fatkhulla (St. Petersburg National Research University of Information Technologies, Mechanics and Optics., 2015)

(untitled)
Compacton matter waves are considered in Bose-Einstein condensates (BEC) and in binary BEC mixtures, trapped in deep optical lattices in the presence of strong and rapid periodic time modulations of the atomic scattering length, are considered. For this, we derive vector averaged discrete nonlinear Schr¨odinger equations (DNLSE) and show that compacton solutions of different types can exist as stable excitations. Stability properties are studied by linear analysis and by direct numerical integrations of the DNLSE system